Paper Modeling of Wind-Solar Hybrid Power System for Off-Grid in Nepal and a Case Study - Thapa, Khagendra Bahadur; Maharjan, Arbin; Kaphle, Kishor; Joshi, Kishor; Aryal, Tara (Journal of the Institute of Engineering, 2020)
The adaptation of renewable energy has been increasing in a very encouraging way all over the world. Among various renewable energy resources, wind and solar energy are the promising sources of alternative energy. Wind and solar photovoltaic (PV) have been employed in parallel as a hybrid system for better electricity service. This paper presents a case study and modeling of wind-solar hybrid system in Hriharpur Gadi village, Sindhuli District, Nepal. The hybrid system yields 110kWh of energy per day meeting the village’s electricity demand of 87 kWh per day. Moreover, the hybrid power system with battery storage system is modeled using MATLAB simulator. Further, improvising in the existing modeling has been presented to enhance the efficiency and effectiveness of the system.